If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 6) = -10 Reorder the terms: 3(6 + x) = -10 (6 * 3 + x * 3) = -10 (18 + 3x) = -10 Solving 18 + 3x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 3x = -10 + -18 Combine like terms: 18 + -18 = 0 0 + 3x = -10 + -18 3x = -10 + -18 Combine like terms: -10 + -18 = -28 3x = -28 Divide each side by '3'. x = -9.333333333 Simplifying x = -9.333333333
| -26=2k+4k | | 105-5x=9x-23 | | 3(1-7d)=33 | | 3(n-5)=14 | | 6(5+4r)=25 | | -4(9x-7)= | | -4aaa+2aaa-6aaa= | | (xxxxxxx)7= | | 2c-4+8=-15 | | x+(2x-21)=180 | | (x+16)+(5x-16)=90 | | -6(7y-4)=31-3y | | 3(4x-6)-4-(2x+5)= | | 4(-5+x)=15+3x | | 2x-13+4x=-1+6(x-2) | | 4(-5+x)=15+3 | | 25=-4(8a+2) | | -25=-3+8(x-4) | | 2n+5n=-28 | | 4x^4+33X^2+8=0 | | 21-5v=8(6v-9) | | 2(x-8)=6(x+2) | | 37=7+62 | | -9c-7-3=-29 | | 129-2x=25x+18 | | (6x-2)-(3x-1)=29 | | 3x+5=25-x | | x^3-10x^2+36x-36=0 | | 7(2-5x)=30 | | 50=16f+2 | | 24+9d=-3 | | -5a-6a=-15 |